2018
DOI: 10.1177/1048291118759303
|View full text |Cite
|
Sign up to set email alerts
|

Labor-Management Cooperation in Illinois: How a Joint Union Company Team Is Improving Facility Safety

Abstract: This study of Afton Chemical Corporation's Sauget facility and its International Chemical Workers Union Council (ICWUC) Local 871C demonstrates how significant safety improvements can be made when committed leadership from both management and union work together, build trust, train the entire work force in U.S. Occupational Safety and Health Administration 10-hour classes, and communicate with their work force, both salaried and hourly. A key finding is that listening to the workers closest to production can l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Two other ICWUC studies reported success in systematically addressing worksite hazards after joint labor management programs trained the entire workforce in OSHA classes assisted by site trainers (Mahan et al, 2014 andMahan et al, 2018). This paper moves a step beyond to explore increased learning and activism from the continuing presence of a group of worker trainers on the shop floor, building an increasing infrastructure for making safety and health integral to daily activities.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Two other ICWUC studies reported success in systematically addressing worksite hazards after joint labor management programs trained the entire workforce in OSHA classes assisted by site trainers (Mahan et al, 2014 andMahan et al, 2018). This paper moves a step beyond to explore increased learning and activism from the continuing presence of a group of worker trainers on the shop floor, building an increasing infrastructure for making safety and health integral to daily activities.…”
Section: Literature Reviewmentioning
confidence: 93%
“…The first two examined pre- and posttraining activities by class participants (Becker and Morawetz 2004, 63-70; McQuiston 2000, 584-597). The latter two (Mahan et al 2018, 227-239; Mahan et al 2013, 561-576) discuss the importance of facility-wide OSHA ten-hour training with local authorized trainers. While ultimately the responsibility for safe and healthful work places is with the employer, active and educated workers help to improve the work environment, these studies all found that after training, workers are more active participants in improving their health and safety, are more willing to attempt to change worksite conditions following training, and their efficacy at making changes is substantially greater than before they were trained.…”
Section: The Literaturementioning
confidence: 99%